Penerapan Fungsi Sistem Pengendalian Manajemen Terhadap Kinerja Karyawan Pada PT. Andalan Inti Indonesia - Yohana Fransiska Natalia; Ni Luh Ayu Atmi Kamaratih; Hwihanus Hwihanus (International Forum of Researchers and Lecturers, 2024)
PT Andalan Inti Indonesia is a company operating in the retail sector. In running a business, a company needs to pay attention to the management control system. As one part of carrying out management functions, planning cannot be separated from control. The management control system itself has the aim of planning, evaluating and making decisions in order to develop and maintain the company's survival. The method used in this research is descriptive qualitative. The results of data analysis show that the strategic planning process at PT Andalan Inti Indonesia is good and budget preparation is carried out per division as well as to make it easier to detail the budget for activity needs. Based on the results of the analysis, it can be concluded that the implementation of the management system control function at PT Andalan Inti Indonesia is quite good and running well. The company has focused on increasing brand awareness as a step in achieving its sales target of 2 billion. Apart from marketing its products offline, the company also utilizes technology that supports the popularity of the online market. Employee placement is carried out appropriately to ensure the effectiveness and productivity of each division. Overall, PT Andalan Inti Indonesia has a structured and holistic approach to company management, with a focus on adapting to market changes, evaluating performance, and implementing short-term strategies that are in line with online market trends.